Reducing firearm injury and death : a public health sourcebook on guns - Karlson, Trudy Ann.; Hargarten, Stephen W. (New Brunswick, N.J. : Rutgers University Press, 1997)
Two experts in public health and injury control show readers how guns are products, designed to injure and kill, and how changes in the design, technology, and marketing of firearms can lead to reductions in the number of injuries and fatalities.
Foreword / Stephen P. Teret -- Introduction: Why We Are Writing This Book -- 1. The Scope of the Problem -- 2. Guns and Ammunition: The Basics -- 3. Modern Firearms -- 4. Comparing Firearms -- 5. Injuries from Firearms -- 6. Where Guns Come From -- 7. How Guns Are Currently Regulated -- 8. Strategies for Reducing Deaths and Injuries from Firearms -- App. 1. Factoring Criteria for Handguns -- App. 2. Text of ATF Form 4473 -- App. 3. A List of Concerned Organizations -- App. 4. Where to Find Out More.
Includes bibliographical references (pages 159-166) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Firearms accidents -- Prevention; Firearms -- Design and construction; Firearms -- Marketing; Firearms; Medical policy; Gunshot wounds; Public health; Penetrating wounds; Manufactures; Wounds and injuries; Diseases; Medical care; Social control; Sociology; Social sciences; Firearms; Wounds, Gunshot -- prevention & control; Wounds, Gunshot; Public Health; Wounds, Penetrating; Manufactured Materials; Wounds and Injuries; Disease; Delivery of Health Care; Social Control, Formal; Sociology; Social Sciences; Consumer Product Safety; Health Policy; United States; Patient Care; Armes à feu -- Conception et construction; Politique sanitaire; Armes à feu; Lésions et blessures par armes à feu; Santé publique; Plaies pénétrantes.; Produits manufacturés.; Lésions et blessures; Maladies; Prestation de soins; Contrôle social; Sociologie; Sciences sociales; Soins médicaux.; public health; sociology; social sciences; POLITICAL SCIENCE -- Political Freedom & Security -- Law Enforcement; Wounds and injuries; Sociology; Social sciences; Social control; Public health; Penetrating wounds; Medical policy; Medical care; Manufactures; Gunshot wounds; Firearms